Unveiling the Disruptive Force: Analyzing the Impact of Digital Shopping - Deepa, Arumugam; Elangovan, Arthanari (Mercados y Negocios, 2024)
The present research aims to analyze the influence of digital shopping on the traditional retail industry in Tamil Nadu. The present research executes a quantitative analysis utilizing the SPSS version 23 software package. A structured questionnaire survey technique is employed to gather the data from the traditional retailers in Tamil Nadu. A judgment sampling strategy has been adopted for analysis. The objective of the method is to collect data relating to conventional retailers’ perceptions of the impact of online shopping applications. Descriptive statistics, ANOVA, regression, and Pearson correlation analysis were performed in the research. The study’s outcomes revealed that digital shopping significantly impacts the growth and profitability of the offline retail industry. Furthermore, the study also evaluates the socio-economic and psychological factors prompting the purchasing behavior of consumers in Tamil Nadu. The study recommends that traditional retailers enhance their strategies to improve their business over online retail marketers.